2008
DOI: 10.1029/2007ja012971
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between kinetic and fluid formalisms for convection in the inner magnetosphere

Abstract: [1] In the inner magnetosphere, the plasma flows are mostly slow compared to thermal or Alfvén speeds, but the convection is far away from the ideal magnetohydrodynamic regime since the gradient/curvature drifts become significant. Both kinetic (Wolf, 1983) and two-fluid (Peymirat and Fontaine, 1994;Heinemann, 1999) formalisms have been used to describe plasma dynamics, but it is not fully understood how they relate to each other. We explore the relations among kinetic, fluid, and recently developed ''average'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…However, they also demonstrated that enforcing a Maxwellian in the RCM solution can drastically affect the evolution of pressures and densities. That conclusion was also confirmed using more realistic conditions by Song et al [2008]. By coupling the RCM to the LFM, the effects of energy dependent drifts on MHD quantities, such as pressure and density, are incorporated into the LFM without the problems that accompany artificially enforcing a Maxwellian.…”
Section: Introductionmentioning
confidence: 65%
“…However, they also demonstrated that enforcing a Maxwellian in the RCM solution can drastically affect the evolution of pressures and densities. That conclusion was also confirmed using more realistic conditions by Song et al [2008]. By coupling the RCM to the LFM, the effects of energy dependent drifts on MHD quantities, such as pressure and density, are incorporated into the LFM without the problems that accompany artificially enforcing a Maxwellian.…”
Section: Introductionmentioning
confidence: 65%
“…However, Song et al [2008] have concluded that all these fluid models produce different results from an original RCM model with a non‐Maxwellian distribution function, at least in some test cases. Therefore the description of the inner magnetosphere by fluid models should be done very cautiously.…”
Section: Introductionmentioning
confidence: 96%
“…Much effort was put into understanding the relations between RCM formalism (such as a drift physics formalism) and fluid formalism [ Heinemann , 1999; Heinemann and Wolf , 2001]. Recently, Song et al [2008] established the equivalence of three models: (1) the fluid model of Fontaine et al [1985] and Peymirat and Fontaine [1994] with an additional heat flux describing the energy transfer due to gradient drift; (2) the fluid model of Liu [2006] with an assumption that distribution is Maxwellian; (3) the RCM equations with an assumption that distribution function is not only isotropic as in the original RCM, but also Maxwellian.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge there has been no study of adding the terms prescribed by Heinemann and Wolf [2001] to a global three‐dimensional magnetospheric MHD code in order to try to reproduce the full kinetic physics. There have been studies analyzing this issue in a more local setting, however; recently, such a study [ Song et al , 2008] has shown that as a practical matter such improvements in magnetospheric fluid models could be problematic, as shock waves tend to form in the simulation.…”
Section: Introductionmentioning
confidence: 99%